Cover Image: Volume 20, Issue 3‐4. Issue 3 (12th July 2018) - Kerney, Ryan R.; Hanken, James; Blackburn, David C.
Abstract : The cover image, by Ryan R. Kerney et al., is based on the Research Early limb patterning in the direct‐developing salamander Plethodon cinereus revealed by sox9 and col2a1, DOI:10.1111/ede.12250 .